Restoration of the Sgraffito Decoration of Litomyšl Chateau – Past and Present - Vojtěchovský, Jan; Waisser, Pavel (Michael Imhof Verlag, 2017)
Since 2011, systematic research and monitoring is being carried out on the sgraffito decoration of Litomyšl Chateau, a UNESCO world heritage listed building since 1999. The sgraffitio decoration dates back to between 1568 and 1581, and was subsequently repaired several times. The sgraffito decoration of the chateau brewery was created around 1630. Some of the sgraffito was never covered over, however, most of it was. From the early 1900s, there was an increase in the number of sections uncovered and interventions carried out on the sgraffito of the chateau and neighbouring brewery. The present-day appearance of the sgraffito has been significantly influenced after being extensively uncovered and renovated between 1975 and 1987 under the leadership of the Czech sculptor Olbram Zoubek. In recent years, within the framework of professional discourse, it was agreed that this restoration phase should be respected due to the fact that those that had carried it out were significant artists of the second half of the 20th century, and that it was basically an irreversible intervention. Recently, localized stabilizing interventions have been carried out on almost all of the chateau facades. A complex restoration has been undertaken on the facade of the entrance tower to the brewery, and a model restoration was also carried out on the north tower of the chateau in 2014. Moreover, in 2016, a project for adaptations to the chateau was submitted which would involve complex restoration and construction interventions, thus influencing and, irreversibly altering the, hitherto, familiar appearance of the facade. Questions therefore arise, as to whether such interventions are acceptable today and furthermore, if this issue should not be the subject of a broad professional discourse on an international and local scale.
Sgrafita litomyšlského zámku – vývoj a současnost
Keywords: Sgraffito; Renaissance; Conservation; Restoration; Facades Decoration; Litomyšl Chateau; Sgrafito; Renesance; Restaurování; Výzdoba fasád; Zámek Litomyšl